2022
DOI: 10.1097/prs.0000000000008722
|View full text |Cite
|
Sign up to set email alerts
|

Consensus Recommendations on the Use of Hyaluronic Acid–Based Fillers for Nonsurgical Nasal Augmentation in Asian Patients

Abstract: Background: Nonsurgical nasal augmentation using dermal fillers such as hyaluronic acid is increasing in popularity because of its less invasive nature and shorter downtime compared with traditional surgery. However, the complexity of the nasal vasculature makes it a high-risk procedure without proper training. Appropriate patient and product selection and safer standardized injection techniques are warranted to minimize complications and to achieve reproducible aesthetic results. In this article, recommendati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 60 publications
1
21
0
Order By: Relevance
“…11,13,15,17,19,20 HA fillers are the most commonly used injectables for NSR procedure. 9,13,15,17,19,20 The growing popularity of NSR among patients and physicians might be attributed to the lower costs, short recovery period, reversibility (if done by HA fillers), prompt obvious results, and perceived safety as a semi-invasive procedure compared to surgery. 9,[13][14][15][16][17]19,20 Studies show that NSR is generally safe and the rate of reported side effects is low.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…11,13,15,17,19,20 HA fillers are the most commonly used injectables for NSR procedure. 9,13,15,17,19,20 The growing popularity of NSR among patients and physicians might be attributed to the lower costs, short recovery period, reversibility (if done by HA fillers), prompt obvious results, and perceived safety as a semi-invasive procedure compared to surgery. 9,[13][14][15][16][17]19,20 Studies show that NSR is generally safe and the rate of reported side effects is low.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 Based on the available scientific literature about the anatomic distribution of the mentioned vessels and their branches, injecting deep (supraperichondrial or supraperiosteal) at the midline of the nose is recommended to minimize vascular complications. 8,9,11,[13][14][15][16][17][18] To challenge the recommended layer of injection in primary NSR (deep at midline), we studied the vascular pattern of the nose of a group of our aesthetic clinic clients using a linear portable 14 MHz handheld ultrasound transducer with Doppler properties (Silarious L14PS HD Portable Doppler Ultrasound Scanner). All study population were Iranian women selected by convenience sampling from January to March 2023.…”
Section: Materials S and Me Thodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The unique viscosity and high rheological affinity for natural fluids has rendered a high interest in cross-linked HA in a wide range of biomedical applications, such as destruction preventer and restoration initiator of cartilage during osteoarthritis [56] , [57] , eye drops for dry eye syndrome [58] , [59] , and dermal fillers [60] , [61] .…”
Section: Ha Applicationmentioning
confidence: 99%
“…Hyaluronic acid (HA) has strong hydrophilic properties and is a commonly used nonsurgical filler 1 . HA injections are considered safe but, in rare cases, may lead to complications of vascular embolism, cerebral infarction, and visual impairment 2 . These complications usually occur immediately after the onset of vascular embolism.…”
Section: Introductionmentioning
confidence: 99%